2016
DOI: 10.1007/s10260-016-0363-x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity, school-effects and the North/South achievement gap in Italian secondary education: evidence from a three-level mixed model

Abstract: With the aim of assessing the extent of the differences in the context of Italian educational system, the paper applies multilevel modeling to a new administrative dataset, containing detailed information for more than 500,000 students at grade 6 in the year 2011/2012, provided by the Italian Institute for the Evaluation of Educational System. Data are grouped by classes, schools and geographical areas. Different models for each area are fitted, in order to properly address the heteroscedasticity of the phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
0
18
0
4
Order By: Relevance
“…Agasisti et al . () and Masci et al . (, ) observed that the percentage of variability in student attainments in INVALSI tests explained by the random effect depends on the geographical macroarea and differs between mathematics and reading performances.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Agasisti et al . () and Masci et al . (, ) observed that the percentage of variability in student attainments in INVALSI tests explained by the random effect depends on the geographical macroarea and differs between mathematics and reading performances.…”
Section: Introductionmentioning
confidence: 86%
“…In this section, we present the semiparametric mixed effects model (Section 2.1), the EM algorithm for the estimation of its parameters (Section 2.2) and a simulation study (Section 2.3). Since we know from previous research on Italian data that there are patterns of student achievements across different Italian schools (Agasisti et al ., ; Masci et al ., , ), we are interested in evaluating how the association between previous and current student test scores changes across different Italian schools and, in particular, in identifying subpopulations of schools within which this association is identical. Therefore, the model that we develop is a two‐level linear model (in the application, students represent level 1 and schools represent level 2) with a discrete distribution with a finite number of support points on the random effects.…”
Section: Model Methods and Simulation Studymentioning
confidence: 99%
See 3 more Smart Citations